2009
DOI: 10.1124/mol.109.060038
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Retinoic Acid Receptors by Dihydroretinoids

Abstract: Vitamin A-derived metabolites act as ligands for nuclear receptors controlling the expression of a number of genes. Stereospecific saturation of the C 13 -C 14 double bond of all-transretinol by the enzyme, retinol saturase (RetSat), leads to the production of (R)-all-trans-13,14-dihydroretinol. In liver and adipose tissue, expression of RetSat is controlled by peroxisome proliferator-activated receptors (PPAR) ␣ and ␥, respectively. Expression of RetSat in adipose tissue is also required for PPAR␥ activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
(68 reference statements)
1
31
0
Order By: Relevance
“…This pathway also involves RALDHs and produces 13,14-dihydro-retinoic acids, which act also as low-affinity RAR ligands (40)(41)(42). We found that retinol saturase is expressed in the thymus, and its expression is induced after in vivo apoptosis induction, indicating that this alternative pathway might be involved in the formation of the novel retinoids.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This pathway also involves RALDHs and produces 13,14-dihydro-retinoic acids, which act also as low-affinity RAR ligands (40)(41)(42). We found that retinol saturase is expressed in the thymus, and its expression is induced after in vivo apoptosis induction, indicating that this alternative pathway might be involved in the formation of the novel retinoids.…”
Section: Discussionmentioning
confidence: 75%
“…Dihydroretinol can be converted further via RALDHs to dihydro-retinoic acids (41), which can also act as low-affinity RAR ligands (42). We therefore investigated whether retinol saturase is expressed in the thymus and whether its expression is enhanced after in vivo apoptosis induction.…”
Section: Macrophages Engulfing Apoptotic Cells Do Not Produce the Clamentioning
confidence: 99%
“…RetSat catalyzes the synthesis of ATRA to all- trans -13,14-dihydroretinol, which can be further converted to all- trans -13,14-dihydroretinoic acid, which is an RAR ligand [78,79], but that has a lower transactivation efficiency compared with ATRA in vivo . Interestingly, RetSat is necessary for 3T3-L1 adipocyte differentiation, and the expression level of RetSat is diminished in the adipose tissue of obese individuals [80], while RetSat knock-out animals have increased adiposity [81].…”
Section: Vitamin Amentioning
confidence: 99%
“…Oxidized metabolites of RA. RA is metabolized by cytochrome P450 enzymes and its oxidized metabolites also activate RAR [141, 142]; however, the function of these RA derivatives in adipose tissue has not been reported.…”
Section: Intra/paracrine Effects Of Retinoic Acid Production From Vitmentioning
confidence: 99%